2020
DOI: 10.1007/s12187-020-09759-z
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Cultural Constraints in Protecting Child Rights in a Society in Transition: A Review and Synthesis from Oman

Abstract: In line with international best practice, the Arabian Gulf countries have ratified the Convention on the Right of the Child (CRC), which has some clauses on child abuse and neglect. The present discourse, made from within an Arabian Gulf society, specifically Oman, reviews the socio-cultural differences of the region and explores the potential regional challenges for effectively implementing the CRC mandated child protection legislation. The international best practices evolved for individualistic, "guilt-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 114 publications
1
24
0
Order By: Relevance
“…In line with the first hypothesis, each type of bullying was significantly and positively correlated with both externalizing and internalizing problems. This is consistent with previous research that has demonstrated that increased levels of bullying victimization are associated with various mental health symptoms [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 73 , 74 ].…”
Section: Discussionsupporting
confidence: 93%
“…In line with the first hypothesis, each type of bullying was significantly and positively correlated with both externalizing and internalizing problems. This is consistent with previous research that has demonstrated that increased levels of bullying victimization are associated with various mental health symptoms [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 73 , 74 ].…”
Section: Discussionsupporting
confidence: 93%
“…A similar paper using more recent data by Steinbach et al (2020) found that adolescents experiencing joint physical custody after their parents' separation reported higher levels of life satisfaction than adolescents from asymmetric care arrangements. However, after controlling for family characteristics (family affluence, the existence of stepparents, and difficulties regarding the communication with both mother and father), the differences between adolescents’ life satisfaction in symmetric JPC and asymmetric care arrangements lost significance.…”
Section: Resultsmentioning
confidence: 82%
“…Under service learning, students are expected to fulfill both the identified community needs and educational goals. Therefore, both service recipients and service providers will benefit from the activities [ 9 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The service targets are children and adolescents with various special needs who live in Hong Kong and mainland China. In Hong Kong, the service targets include school children and adolescents with emotional or behavioral problems from Society of Boy’s Centres, pre-school children with intellectual difficulties or development disorders from Heep Hong Society, and adolescents from local schools who are underachieving academically with social deprivation [ 11 , 20 ]. Service activities are designed according to the specific needs of the service targets, such as tutorial, extracurricular class, day camp, and campus visit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation